Market discipline across bank governance models: Empirical evidence from German depositors - Eva A. Arnold; Ingrid Größl; Philipp Koziol (Hamburg University, Department Socioeconomics, 2015)
German savers are renowned for preferring safe, long-term investments, thus providing patient capital, with bank deposits playing an important role. Using a unique data set provided by the Deutsche Bundesbank for German banks, we examine whether German depositors are really that patient, abstaining from any type of market discipline, and how the financial crisis might have changed a well-established habit. Our empirical investigation reveals the existence of market discipline with a high degree of heterogeneity depending on banks' governance structures. The announcement of a state guarantee for bank deposits following the collapse of Lehman Brothers succeeded in calming depositors of all banking groups but did not remove market discipline entirely. Remaining disciplinary reactions by depositors of different banking groups increase in homogeneity but some differences remain.
Keywords: G10; G20; G30; 330; market discipline; bank depositor behavior; bank risk taking; deposit rates